New Methods of Treatment of the Burned (Literature Review) (Texas Journal of Medical Science, 2022)
Over the past decades, new methods of treating burn wounds based on biotechnology have appeared. The review presents the main materials for the treatment of burns, which were created using tissue engineering - biological wound dressings and skin substitutes.